EXCITATION CHARACTERISTICS OF THE SQUID GIANT AXON: A TEST OF EXCITATION THEORY IN A CASE OF RAPID ACCOMMODATION - LeFevre, Paul G. (The Rockefeller University Press, 1950)
1. The characteristics of the threshold excitation behavior of the squid giant axon were investigated with condenser discharges, exponentially blunted D. c. shocks, sinusoidal currents, and brief condenser-discharge test shocks superimposed at either electrode at controlled brief intervals following the closing of a constant current. 2. Data obtained by the use of condenser discharges and exponentially blunted currents followed theoretical patterns separately, but could not be mutually reconciled, under the system of the two-factor theories of excitation, since the accommodation was so rapid that the apparent ratio between the two time factors was incompatible with certain previously neglected theoretical limitations. 3. Data obtained with the other procedures indicated similarly rapid accommodation, but usually showed an imaginary component in the values of the time constants, associated with a capacity of the threshold to exhibit damped oscillatory behavior. 4. The anodal threshold behavior did not parallel that at the cathode, showing neither oscillation nor accommodation at ordinary current intensities. 5. The digressions from predictions of the two-factor theories of excitation are partly analyzed and compared with other reported deviations.